Let me remind first the construction of Brownian motion.

Fix a vector $x \in \mathbb{R}^n$ and define $p(t,x,y) := (2\pi t )^{-\frac{n}{2}} \cdot \exp{\left( - \frac{|x-y|^2}{2t} \right)},$ for $y \in \mathbb{R}^n$, $t >0$.

Then for $0 \leq t_1 \leq t_2 \leq \ldots \leq t_k$ we define a measure $\nu_{t_1, \ldots, t_k}$ on $\mathbb{R}^{nk}$ by $$\nu_{t_1, \ldots, t_k}(F_1 \times \ldots \times F_k)= \int \limits_{F_1 \times \ldots \times F_k}^{} p(t_1, x, x_1)\prod_{j=1}^{k-1}p(t_{j+1}-t_j,x_{j}, x_{j+1}) dx_1\ldots dx_k,$$ where the following conventions are used $dy=dy_1\ldots dy_k$ for Lebesgue measure and $p(0, x, y)dy=\delta_x(y)$ (the unit point mass at $x$).

By Kolmogorov's extension theorem applied to the probability measures $\nu_{t_1, \ldots, t_k}$ (which easily satisfies all the assumtions of that theorem) there exists a probability space $(\Omega, \mathcal{F}, P^x)$ and a stochastic process $\{B_t\}_{t \geq 0}$ on $\Omega$ such that the finite distributions of $B_t$ are given by $$ (\star) \ \ P^x(B_{t_1} \in F_1, \ldots, B_{t_k} \in F_k)= \int \limits_{F_1 \times \ldots \times F_k}^{} p(t_1, x, x_1)\prod_{j=1}^{k-1}p(t_{j+1}-t_j,x_{j}, x_{j+1}) dx_1\ldots dx_k.$$


I want to show that for the random variable $Z = (B_{t_1}, \ldots, B_{t_k}) \in \mathbb{R}^{nk}$ there exist a vector $M \in \mathbb{R}^{nk}$ and a non-negative definite matrix $C \in \text{M}_{nk \times nk}(\mathbb{R})$ such that $$E^x\left[\exp\left(i\left<u, Z \right> \right)\right]= \exp\left( -\frac{1}{2} \left<Cu, u\right> + i \left<u, M\right> \right),$$ for all $u=(u_1, \ldots, u_{nk}) \in \mathbb{R}^{nk}$ (left hand side stands for the characteristic function of the random variable $Z$). Moreover, $M$ is the mean value of $Z$ and $C$ is a covariance matrix of $Z$.

I was trying to calculate it explicitly by writing the left hand side by its definition and applying the ($\star$) formula, but the integral which I've got is not so nice and I cannot conclude what I want to.

This exercise is nothing else, but showing that $B_t$ is a Gaussian process (so it is not hard to guess what should be $M$ and $C$ in this case).

I hope you know some tricks how to compute such an integral in an easy way. Thanks in advance for any help.

  • $\begingroup$ I think it suffices to show that the integral will indeed be of the form $\exp( -\frac{1}{2} \langle C u, u \rangle + i \langle u, M \rangle)$. It would then follow that $C$ and $M$ are covariance and mean. This is a trivial excercise in integration of a Gaussian. To carry it out, write $\langle u, Z \rangle = \sum_{i=1}^n u_i \sum_{k=1}^i X_k$ where $X_k$ are corresponding independent normal variates corresponding to $B_{t_i-t_{i-1}}$. It would then follow that c.f. is a product of exponentials of quadratics. $\endgroup$ – Sasha Aug 25 '11 at 16:17
  • $\begingroup$ If I show the the characteristics function of $Z$ is of above form it implies that $B_t$ is a Gaussian process. By using the form of $M$ and $C$ we easily got that $E^x(B_t)=x$ and $E^x((B_t-x)(B_s-x))=n \mbox{min}\{s,t\}$ which gives us that $B_t$ has independent increments (equivalently, uncorrelated for normal distribution are independent). I think that your hint already involves that $B_t$ is normal distributed and it has independent increments, which is a further consequence of the fact I want to show. Am I right? $\endgroup$ – Franz Aug 25 '11 at 17:27
  • $\begingroup$ I mean consider integration of $ \exp( i \sum_{k=1}^n u_k t_k )$. Because $t_i-t_{i-1}$ occur naturally in your measure, change variables, by letting $t_i = \sum_{m=1}^i s_m$. Your measure then becomes a product of independent Gaussians which you can carry out. Integration w.r.t. each $s_m$ will produce $e^{\text{quadratic in} u}$, hence their product will again be quadratic in $u$. $\endgroup$ – Sasha Aug 25 '11 at 17:58
  • $\begingroup$ Ok, I understand. Probably, above you had some notation issue. We should denote $u_j := (u_1^j, \ldots, u_n^j) \in \mathbb{R}^n$ and now $$E(\exp(i \left< u, Z\right>) = \int_{\mathbb{R}^{nk}} \exp(i \sum_{j=1}^k u_jx_j) p(t_1, x, x_1) \prod_{j=1}^{k-1}p(t_{j+1}-t_j, x_j, x_{j+1})dx_1 \ldots dx_k.$$ Now, we should substitute $x_j = \sum_{m=1}^{j}\hat{x}_m$ and with this substitution we can easily separate the integrals. I think you can write this as the answer. $\endgroup$ – Franz Aug 25 '11 at 20:46

Denote $t_0 = 0$ and $x_0 = 0 $ for notational convenience. Then

$$ \mathbb{E}( \exp(i \langle u, Z \rangle ) = \int_{\mathbb{R}^{n k}} \exp( i \langle u, x \rangle ) \prod_{j=1}^k p(t_{j}-t_{j-1}, x_{j} - x_{j-1}) \mathrm{d}x_1 \cdots \mathrm{d} x_k $$ Now change variables $x_k = \sum_{i=1}^k s_k$. This has unit Jacobian, you get $$ \mathbb{E}( \exp(i \langle u, Z \rangle ) = \int_{\mathbb{R}^{n k}} \prod_{k=1}^k \exp( i \, s_j \sum_{m=j}^k u_q ) ) \prod_{j=1}^k p(t_{j}-t_{j-1}, s_j) \mathrm{d}s_1 \cdots \mathrm{d} s_k $$ Now integration with respect to each $s_j$ can be carried out independently and will produce $\exp( Q_j(u))$, where $Q_j$ is a quadratic multivariate polynomial in $u$. Hence the characteristic function of k-dimensional time-slice distribution of this Brownian motion process is going to be $\exp(Q(u))$.

Now $Q(u) = \langle C u, u \rangle + i \langle u, M \rangle $, where $C$ is covariance matrix and $M$ is mean vector. The free term will be missing, because c.f. is one for zero vector $u$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.